O incidente de desconsideração da personalidade jurídica no processo do trabalho: aspectos teóricos e práticos a partir das previsões da Lei n. 13.105/2015 e da Lei n. 13.467/2017 - Gomide, Renata Rechden (2019)
The objective of this study is to analyze the theoretical and practical consequences of the institute of the disregard of legal personality in labor law in view of the determinations contained in law n. 13.467/2017, which determined the application of the procedure set forth in arts. 133 to 137, of Law no. 13.105/2015, here treated as a procedural incident. Aiming at contextualizing the topic, it presents a panorama of basic issues, such as the super privileged condition of labor credit, its generating fact and the main responsible for its compliance, as well as some possible responsible for the satisfaction of labor credit. It will be approached the emergence of the theory of disregard of legal personality, the compatibility between the rules of civil procedural law and the process of labor, which has as a part the figure of the hyposufficient. Criticism will be made of the labor reform, which has simply brought the necessary contradiction to the employer, but has failed to regulate the subject in the scope of substantive law. The relevance of the analysis is justified in view of existing doctrinal and jurisprudential divergences, with consequent relevance in the area oflegal certainty, which led to the acceptance of the civilian incident, since a uniform all cases that contain the subject. The applied method was the deductive one, using bibliographical and jurisprudential research related to the subject, demonstrating the lack of cohesion for the subject, leading to the finding that it is necessary to harmonize the subject by observing the rules laid